2019
DOI: 10.3390/agronomy9080436
|View full text |Cite
|
Sign up to set email alerts
|

The Clogging Rules of Ceramic Emitter in Irrigation Using Saline Water with Different EC

Abstract: Infiltration irrigation with saline water is a more effective method than drip irrigation to alleviate water scarcity worldwide, but so far, no report has discussed the clogging rules of ceramic emitters, a major component of infiltration irrigation system. To explore the clogging mechanism of ceramic emitter in saline water infiltration irrigation system, we used four kinds of saline water sources with electrical conductivity (EC) of 0.18, 1.74, 3.78, and 7.74 ds/m, respectively. In addition, we specifically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…Chemical clogging of emitters does not occur suddenly. It is caused by the long-term accumulation of the clogging substances [62,63]. There are randomness and fluctuations in the flow rate of a single emitter [26].…”
Section: Research Progress and Mechanism On The Chemical Clogging Of ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical clogging of emitters does not occur suddenly. It is caused by the long-term accumulation of the clogging substances [62,63]. There are randomness and fluctuations in the flow rate of a single emitter [26].…”
Section: Research Progress and Mechanism On The Chemical Clogging Of ...mentioning
confidence: 99%
“…There are randomness and fluctuations in the flow rate of a single emitter [26]. Chemical clogging processes can be categorized as gradual, fluctuating, or sudden reductions of emitter discharge [26,62,64], in which the sudden reductions in flow are normally observed in the high salinity water. Overall, the discharge of emitters shows a gentle fluctuation trend at first, and then a sharp decline with the operation of the system [20].…”
Section: Research Progress and Mechanism On The Chemical Clogging Of ...mentioning
confidence: 99%
“…Os precipitados químicos podem ser produzidos ao se modificar as condições iniciais da água tais como o pH, temperatura, presença de íons incompatíveis e devido à evaporação da água nos emissores após cada irrigação, aumentanto a concentração dos sais ao ponto de ultrapassar o limite da sua solubilidade. As obstruções químicas mais frequentes são de originados de precipitados de carbonatos de cálcio (RIZK et al, 2019) ou sulfato de cálcio (CHEN et al, 2019b). O risco de obstruções não depende somente das concentrações destes componentes, mas também do regime hidráulico, das dimensões e da forma dos emissores.…”
Section: Caracterização Do Problemaunclassified
“…A study discovered that saline water clogging is a gradual process (Zhangzhong et al, 2021). Additionally, the higher the electrical conductivity of irrigation water is, the more severe the emitter clogging, and CaCO 3 is the main factor for clogging (Chen et al, 2019; Zhangzhong et al, 2021). Research has shown that the desalinated saline water salinity threshold should be kept below 5 g/L to maintain the favourable anti‐clogging performance of drip irrigation (Liu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%